Propaganda & persuasion - Jowett, Garth; O'Donnell, Victoria (SAGE Publications, Inc., 2019)
"Reflecting the remarkable changes in the world of propaganda due to the increasing use of social media, this updated Seventh Edition provides a systematic introduction to the increasingly complex world of propaganda. Viewing propaganda as a form of communication, the authors help you understand information and persuasion so you can understand the characteristics of propaganda and how it works as a communication process. Providing provocative case studies and fascinating examples of the use of propaganda from ancient times up through the present day, Propaganda and Persuasion provides an original model that helps you analyze the instances of propaganda and persuasion you encounter in everyday life"--Provided by publisher.